Late progression of pediatric Kikuchi-Fujimoto disease to systemic lupus erythematosus: a case report and review of literature - Bessioud, Salma; Tlili, Karima; Barakizou, Hager; Mezri, Sameh (Frontiers in Immunology, 2026)
BackgroundKikuchi-Fujimoto disease (KFD) is a rare, self-limiting lymphadenitis predominantly affecting children and young adults, often mimicking lymphoma or tuberculous lymphadenitis. Although it usually resolves spontaneously, KFD has occasionally been associated with autoimmune disorders, particularly systemic lupus erythematosus (SLE).CaseWe report a six-year-old girl presenting with persistent cervical lymphadenopathy, low-grade fever, fatigue, and weight loss. Laboratory evaluation showed mild leukopenia and elevated erythrocyte sedimentation rate, while autoimmune markers were initially negative. Excisional lymph node biopsy confirmed KFD. She responded well to initial oral corticosteroid therapy, with complete regression of lymphadenopathy, though two recurrences occurred during follow-up, managed by a short course of corticosteroids once and resolved spontaneously on the other occasion. Remarkably, 12 years later, she presented with fatigue, arthralgia, and malar rash. Laboratory evaluation revealed cytopenias, proteinuria, and positive ANA and anti-dsDNA antibodies, leading to a diagnosis of SLE.ConclusionThis case highlights the potential long-term autoimmune risk following KFD and emphasizes the importance of sustained clinical and immunological follow-up in pediatric patients for early detection and timely management.